Modeling of the curing kinetics of acrylate photopolymers for additive manufacturing - Setter, Robert; Schmölzer, Stefan; Rudolph, Natalie; Moukhina, Elena; Wudy, Katrin (Polymer Engineering and Science, 2023)
Next-generation additive manufacturing (AM) processes such as multiphoton lithography and the fusion jetting (FJ) process demonstrate increasing demands toward temperature stability and a thoroughly understood curing behavior of acrylate photopolymers. This investigation targets the utilization of different kinetic models based on experimentally determined calorimetric results of different acrylate systems. The goal is to determine a holistic model that successfully describes the simultaneous dependency of the curing behavior on the temperature and the UV intensity. Two consecutive modeling strategies are investigated: a single measurement analysis followed by a clustered measurement analysis. In both cases, models based on the Kamal–Sourour method provide superior coefficients of determination above 0.99. First conclusions were drawn toward selected kinetic parameters, such as the temperature independence of the respective reaction orders. The model was then successfully utilized for first predictions of the curing behavior, demonstrating plausible progressions of the degree of cure for not experimentally determined UV intensities.
CRIS-Team Scopus Importer:2023-06-02
Keywords: additive manufacturing; degree of polymerization; differential scanning calorimetry; kinetics (polym.); photopolymerization